Outcome-Based Quality Control by a Dental Reference Profile of a Population-Based Study (SHIP-0). (2nd July 2015) - Samietz, Stefanie; Söhnel, Andreas; Schwahn, Christian; Holtfreter, Birte; Mundt, Torsten; Meisel, Peter; Hoffmann, Wolfgang; Kocher, Thomas; Biffar, Reiner
Abstract : Objectives . The aim was to develop an instrument for quality control in dental practices. We compared the number of teeth of subjects of the Study of Health in Pomerania (SHIP-0) with those from patients of dental practices. Methods . Patients from seven dental practices( n = 1, 497 ) were randomly sampled by age strata and gender for a period of two years. Dental status derived from patient files was transformed into practice profiles using age-specific number of teeth as a parameter. Practice profiles were compared with a nomogram, which was based on the age-specific number of teeth of 3, 990 SHIP-0 participants regularly visiting the dentist. Further, negative binomial regression models were evaluated to model associations between the number of teeth with age and dental practices, including interactions. Results . The practice profiles ranged between the 45th and 95th quantile curves of the reference population SHIP-0. The rate ratios (RR) for the number of missing teeth ranged from 0.37 to 0.67( p < 0.001 ) between the different dental practices, indicating lower risk for higher numbers of missing teeth in comparison to SHIP-0. Conclusions . This study showed considerable differences between dental practices and the reference population of SHIP-0 regarding the pattern of tooth loss and confirms the value of nomograms to compare age-specific numbers of teeth between patients of dental practices and a population-based-study as a tool for quality control. For further analyses, the socioeconomic status of patients and relevant risk factors will be used to adjust for structural differences in order to improve the validity of the comparisons.